2018
DOI: 10.3233/jad-170814
|View full text |Cite
|
Sign up to set email alerts
|

Erythromyeloid-Derived TREM2: A Major Determinant of Alzheimer’s Disease Pathology in Down Syndrome

Abstract: Background:Down syndrome (DS; trisomy 21) individuals have a spectrum of hematopoietic and neuronal dysfunctions and by the time they reach the age of 40 years, almost all develop Alzheimer’s disease (AD) neuropathology which includes senile plaques and neurofibrillary tangles. Inflammation and innate immunity are key players in AD and DS. Triggering receptor expressed in myeloid cells-2 (TREM2) variants have been identified as risk factors for AD and other neurodegenerative diseases.Objective:To investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 61 publications
3
38
0
Order By: Relevance
“…Plasma sTREM2 was significantly elevated in DS, in agreement with previously described elevation of sTREM2 in DS sera from young adults with DS prior to dementia onset 33 . Interestingly, sTREM2 is elevated in cerebrospinal fluid in the mild cognitive impairment stage of AD and in early onset forms of AD, but not in peripheral biofluids, such as plasma 24,25,27,28,54 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Plasma sTREM2 was significantly elevated in DS, in agreement with previously described elevation of sTREM2 in DS sera from young adults with DS prior to dementia onset 33 . Interestingly, sTREM2 is elevated in cerebrospinal fluid in the mild cognitive impairment stage of AD and in early onset forms of AD, but not in peripheral biofluids, such as plasma 24,25,27,28,54 .…”
Section: Discussionsupporting
confidence: 91%
“…The soluble cleavage product of TREM2 (sTREM2) is elevated in AD cerebrospinal fluid and positively correlates with Aβ and cognitive decline [24][25][26][27][28][29][30][31][32] . There is relatively little information about TREM2 in DS, though one group describes elevated sTREM2 in young adults and declining levels with aging 33,34 .…”
Section: Introductionmentioning
confidence: 99%
“…There have been some studies that report to show human TREM2 immunohistochemistry but with varying results (12,51). Most recently Raha-Chowdhury et al (47,48) have shown some immunohistochemistry with TREM2 in human tissue but it is unknown how well this was characterised. There has been some debate in the field when some of these studies were published that TREM2 was only expressed in monocytes, hence the staining pattern separate to microglia (7,12,51).…”
Section: Discussionmentioning
confidence: 99%
“…A drop of blood placed on a slide was spread using a spreader as described previously [29]. The slide was air-dried and fixed in 100% methanol and stored at 4°C.…”
Section: Blood Slide Preparationmentioning
confidence: 99%
“…We found that CD26 is expressed in the epithelial membrane of the choroid plexus (CP) and in the endothelium of blood vessels in the brain. The CP is a secretory tissue responsible for producing both the CSF in the vertebrate brain and many innate immune molecules to protect the brain from infection by surveilling the blood brain barrier (BBB) [29,68]. CD26 protein is present in the CP epithelial membrane and in the outer layer of brain pia mater particularly in the meningeal macrophages, where it is colocalised with other brain spectrins, known as fordin and ankyrin [29,69].…”
Section: Recently Sequence and Modeling Analysis Of S Glycoproteins mentioning
confidence: 99%